1991
DOI: 10.1111/j.2042-3306.1991.tb02735.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and umbilical venous plasma lipid concentrations at delivery in the mare

Abstract: Summary The concentrations and fatty acid composition of the plasma free fatty acid, triacylglycerol and phospholipid fractions were determined in maternal and umbilical cord vein blood samples taken at delivery from 17 mares. Maternal and umbilical vein plasma free fatty acid concentrations were of a similar order and a positive correlation was found between the two levels suggesting that the equine placenta is permeable to fatty acid. Substantial amounts of the essential fatty acids and their longer chain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In agreement with Stammers et al (1991) we found the percentage of LA markedly lower and of DGLA and AA…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In agreement with Stammers et al (1991) we found the percentage of LA markedly lower and of DGLA and AA…”
Section: Discussionsupporting
confidence: 77%
“…In humans the total lipid concentration is lower in cord blood than in maternal blood at delivery (Ruyle et al 1990), and the absolute amount of AA in umbilical plasma is therefore lower compared with maternal values (Ruyle et al .1990;Al et al 1995). In the horse the content of total blood lipids in foetal venous blood is almost as high as in maternal venous blood (Stammers et al 1991). Therefore the relative composition of total plasma fatty acids reflects the absolute fatty acid status in the horse.…”
Section: Pferdeheilkunde '12mentioning
confidence: 94%
See 2 more Smart Citations
“…First, in humans, fetal pat terns of essential fatty acids and structural lipids correlate directly with the fatty acid/lipid composition of the ma ternal plasma (and, thus, the maternal diet) [45]. While this pattern is found in most mammals, there is some vari ation, as sheep transport very little total lipid except for some long-chain essential fatty acids, and the horse pro duces a lipid profile in the fetal plasma qualitatively and quantitatively different form the maternal plasma [46]. Second, fatter human fetuses develop in pregnant women who have higher plasma concentrations of lipids [47], Third, among species, there is a relatively direct relation ship between placental lipid transport capacity and fetal body fat content [ 1 ].…”
Section: Lipidsmentioning
confidence: 99%